The percentage is calculated by dividing the required value by the totalvalue and multiplying by 100.
Example:
Requiredpercentage value = a
totalvalue = b
Percentage = a/b x 100
100% = $60
35% = $21
The saleprice of the football is $21
The percentage is calculated by dividing the required value by the totalvalue and multiplying by 100.
Requiredpercentage value = a
totalvalue = b
Percentage = a/b x 100
Example:
50% = 50/100 = 1/2
25% = 25/100 = 1/4
20% = 20/100 = 1/5
10% = 10/100 = 1/10
We have,
Originalprice = $60
Sellingprice.
= 35% of $60
= 35/100 x 60
= 7 x 3
= $21
We can also find this way.
100% = $60
35% = 35/100 x $60
35% = $21
Thus,
100% = $60
35% = $21
The saleprice of the football is $21
Learn more about percentages here:
#SPJ5
The length of a rectangular snow fort is 7 feet and the width of a rectangular snow fort is 5 feet.
Given that, Chris Built a rectangular snow fort with a perimeter of 24 feet.
The perimeter of a rectangle is the total distance of its outer boundary. It is twice the sum of its length and width and it is calculated with the help of the formula: Perimeter = 2(length + width).
Let x be the length of a rectangular snow fort and y be the width of a rectangular snow fort.
The length of the fort was 8 feet less than 3 times the width.
y=3x-8
Now, 2(y+x)=24
⇒ 3x-8+x=12
⇒ 4x=20
⇒ x=5
So, y=3x-8=7
Therefore, the length of a rectangular snow fort is 7 feet and the width of a rectangular snow fort is 5 feet.
To learn more about the perimeter of a rectangle visit:
brainly.com/question/15287805.
#SPJ2
Answer:
Step-by-step explanation:
First, let's convert 6 feet 3 inches to just inches. Because there are 12 inches in 1 foot, we can say that there are 72 inches in 6 feet. Combined with the other 3 inches, we can say that Marco is a 75 inches tall.
Now, we can multiply the number of inches we found by 2.54 to get Marco's height in centimeters. This gives us 190.5 cm.
Answer:
192 cm
Step-by-step explanation:
The value of f^-1(3) is 4
The inverse of a function f(x) is the opposite of the function
The functionf(x)is given as:
Express f(x) as y
Swap the positionsof x and y
Express as exponents
Make y the subject
Express the equationsas an inverse function
Substitute 3 for x in the above equation
Evaluate
Hence, the value of f^-1(3) is 4
Read more about inverse functions at:
#SPJ5
Answer:
To multiply the expressions (3x + 2y + 1) and (2x - 3y - 5) vertically, we will use the distributive property and multiply each term from the first expression with each term from the second expression.
Starting with the first term in the first expression, which is 3x, we multiply it with each term in the second expression:
(3x) * (2x) = 6x^2
(3x) * (-3y) = -9xy
(3x) * (-5) = -15x
Next, we move to the second term in the first expression, which is 2y:
(2y) * (2x) = 4xy
(2y) * (-3y) = -6y^2
(2y) * (-5) = -10y
Finally, we multiply the last term in the first expression, which is 1, with each term in the second expression:
(1) * (2x) = 2x
(1) * (-3y) = -3y
(1) * (-5) = -5
Now, let's add up all the results:
6x^2 - 9xy - 15x + 4xy - 6y^2 - 10y + 2x - 3y - 5
Simplifying this expression further, we have:
6x^2 - 5x - 6y^2 - 7xy - 13y - 5
Answer:
To multiply the expressions (3x+2y+1) and (2x-3y-5) vertically, you can use the distributive property and follow these steps:
1. Start by multiplying the first term in the first expression, 3x, by each term in the second expression:
- (3x) * (2x) = 6x^2
- (3x) * (-3y) = -9xy
- (3x) * (-5) = -15x
2. Move on to the second term in the first expression, 2y:
- (2y) * (2x) = 4xy
- (2y) * (-3y) = -6y^2
- (2y) * (-5) = -10y
3. Finally, multiply the last term in the first expression, 1, by each term in the second expression:
- (1) * (2x) = 2x
- (1) * (-3y) = -3y
- (1) * (-5) = -5
Now, let's combine the like terms:
6x^2 + (-9xy) + (-15x) + 4xy + (-6y^2) + (-10y) + 2x + (-3y) + (-5)
Simplifying this expression further, we have:
6x^2 - 5x - 9xy + 4xy - 6y^2 - 10y + 2x - 3y - 5
Therefore, the result of multiplying (3x+2y+1) and (2x-3y-5) vertically is 6x^2 - 5x - 9xy + 4xy - 6y^2 - 10y + 2x - 3y - 5.
Step-by-step explanation: